Tunable Q-switched thulium-doped fiber laser (TDFL) in 2.0 µm region based on gallium selenide saturable absorber - Ahmad, Harith; Reduan, Siti Aisyah (Elsevier, 2018)
A tunable Q-switched thulium-doped fiber laser (TDFL) using a Gallium Selenide (GaSe) based saturable absorber (SA) is proposed and demonstrated for operation in the 2.0 µm region. The Q-switched TDFL operates from 1960.0 nm to 1998.0 nm, covering a wavelength range of 38.0 nm. The generated output pulses have a repetition rate from 14.9 kHz to 40.9 kHz and minimum pulse width of 4.9 µs at the maximum pump power of 126.6 mW, as well as a maximum pulse energy of 92.8 nJ. This is, to the author's knowledge, the first successful combination of a TDF and a GaSe based SA to generate tunable Q-switched pulses in 2.0 µm region.